(untitled) (Global Journal of Science Frontier Research, 2024)
Background The global transportation sector is facing increasing challenges related to air pollution greenhouse gas emissions and climate change As a result there is a growing need to shift towards cleaner and more sustainable modes of transportation Electric vehicles EVs have gained significant attention as a promising solution to reduce emissions and dependence on fossil fuels Central to the operation of EVs are lithium-ion batteries which provide the necessary energy storage capacity for electric propulsion Lithium-ion batteries have emerged as a leading technology in the field of energy storage due to their high energy density low self-discharge rate and versatile design options However ensuring the reliability and safety of these batteries remains a critical aspect for the widespread adoption of EVs Figure 1 explain the Electric Vehicle architecture in details